A hard day [videorecording (DVD)] - Kim, Sŏng-hun, 1971-; Yi, Sŏn-gyun, 1975-; Cho, Chin-ung, 1976-; Sin, Chŏng-gŭn, 1965- (Kino Lorber, 2015)
"A pitch-black comedy with style to burn, A Hard Day depicts a day-in- the-life of a cop that goes from bad to worse to cursed. Driving back from his mother's funeral, homicide detective Gun-soo runs over a man in a dark rural street. In a moment of desperation, he dumps the body in a coffin alongside his mother. The disappearance of his accident victim is investigated by a colleague, and, making matters worse, a witness steps forward, a detective named Park."--Container.